An Overview on Potential Neuroprotective Compounds for Management of Alzheimer's Disease - Ahmed Sheikh, Ishfaq; Ali, Riyasat; A. Dar, Tanveer; Amjad Kamal, Mohammad (CNS & Neurological Disorders - Drug Targets, 2012)
Alzheimer's disease (AD) is one of the major neurodegenerative diseases affecting almost 28 million people around the globe. It consistently remains one of the major health concerns of present world. Due to the clinical limitations like severe side effects of some synthesized drugs, alternative forms of treatments are gaining global acceptance in the treatment of AD. Neuroprotective compounds of natural origin and their synthetic derivatives exhibit promising results with minimal side effects and some of them are in their different phases of clinical trials. Alkaloids and their synthetic derivatives form one of the groups which have been used in treatment of neurodegenerative diseases like AD. We have further grouped these alkaloids into different sub groups like Indoles, piperdine and isoquinolines. Polyphenols form another important class of natural compounds used in AD management.
Keywords: Alzheimer' s disease